2021
DOI: 10.1016/j.adolescence.2021.08.009
|View full text |Cite
|
Sign up to set email alerts
|

The outcomes of sexting for children and adolescents: A systematic review of the literature

Abstract: Introduction: Given associated risks, sexting among children and adolescents has yielded significant interest in recent years. Several previous reviews have examined data on the prevalence, determinants, and correlates of sexting behaviour, however, in an ever-changing digital media context, a comprehensive overview of findings regarding its outcomes is warranted. This novel review aimed to systematically identify and conduct a narrative synthesis of empirical evidence regarding the outcomes of sexting involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 88 publications
1
36
0
2
Order By: Relevance
“…A meta-analysis of 39 sexting studies with adolescent samples in various countries revealed that 14.8% of youth had sent a sext and 27.4% had received a sext (Madigan et al, 2018). Sexting can be motivated by various purposes, including the desire to harm others (i.e., cyberbully) by sharing compromising or private photos to a wide audience (Bauman, 2011; Doyle et al, 2021; Harris & Davidson, 2014). In these cases, school counselors may be involved in supporting the victim, working with the perpetrator, or addressing the parents and family members of students involved (McEachern et al, 2012).…”
Section: Sexting Behaviors Among Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of 39 sexting studies with adolescent samples in various countries revealed that 14.8% of youth had sent a sext and 27.4% had received a sext (Madigan et al, 2018). Sexting can be motivated by various purposes, including the desire to harm others (i.e., cyberbully) by sharing compromising or private photos to a wide audience (Bauman, 2011; Doyle et al, 2021; Harris & Davidson, 2014). In these cases, school counselors may be involved in supporting the victim, working with the perpetrator, or addressing the parents and family members of students involved (McEachern et al, 2012).…”
Section: Sexting Behaviors Among Adolescentsmentioning
confidence: 99%
“…Another behavior influenced by the availability and advancement of technology is sexting, defined as the “transmission of sexually explicit text messages, images, and/or videos to others via electronic/digital communication technologies” (Doyle et al, 2021, p. 90). Among U.S. adolescents, 14% reported receiving a sext from a romantic partner and 13.6% reported receiving a sext from someone who was not a romantic partner (Patchin & Hinduja, 2019).…”
mentioning
confidence: 99%
“…The outcome of sexting is wide, ranging from positive and accepted to negative and unwanted [75]. The photos produced for sexting can be distributed to a wider audience, often leading to embarrassment, harassment, and placing adolescents in vulnerable positions [76].…”
Section: ) Conduct Riskmentioning
confidence: 99%
“…The link between mental health and online risk is wellestablished, though the relationship between the two appears complicated. Online risks have been identified as having a negative impact on young people's mental health (Doyle et al, 2021), but are also more prevalent amongst those internet users with pre-existing mental health difficulties (Vandoninck et al, 2013). Research among adolescents has found that poorer psychological wellbeing, self-esteem, and self-control are related to the severity of problematic internet use (Mei et al, 2016).…”
Section: Introductionmentioning
confidence: 99%